(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Information Technologies (IT) create interconnected application software. Nowadays, one of the vital problems is the enterprise application software integration. Systems of the transport routing become more complicated, because in order to efficiently solve transport routing and planning problems, it is necessary to get more and more information. Enterprise application methods and technologies allow to create effective transport routing system. To structure integration solutions, can be used different options and solutions, as well as platform of integration, but vital problem is the choice of the most suitable integration approach. The aim of this paper is to evaluate several accessible integration solutions. Integration options are identified and classified according to integration approach and technologies used in this paper. In practical assessment of integration technologies, post parcel delivery and routing process is used as an example, for which it is necessary to create effective GPS/GIS/ERP integration solution. For this problem, several alternative solutions have been developed. They have been evaluated according to their high-speed, easily of development and modification, as well as other parameters.